Design optimization of a cross-flow He-Xe recuperator through second law analysis. (1st October 2020) - de Araújo, Élvis F.; Ribeiro, Guilherme B.; Guimarães, Lamartine N.F.
Highlights: A He-Xe recuperator was designed from a prior turbomachine CAD model. A two-stream CFD heat-exchanger modeling was applied for design optimization. Several geometries were simulated under various mass flow rates. Optimum mass flow rates were obtained based on the entropy generation number. Geometry definition was carried out by means of a mass/performance analysis. Abstract: Nuclear power conversion in space has been approached by various means since the first space missions, with the advent of concepts such as thermoelectric, thermionic and thermodynamic conversion. Nowadays, thermal cycles are under greater focus for being capable of providing higher conversion efficiencies. In this context, one of the main concerns of engineers is the trade-off between power and mass. Therefore, this work aims the optimization of a recuperator used in a regenerative closed Brayton cycle applied for power conversion in the project of a small-scale nuclear reactor. The recuperator consists of a cross-flow, shell-and-tube heat exchanger with a matrix of tubes distributed in a staggered configuration. In this work, the number of tubes and the mass flow rate are varied. The number of tubes distributed axially is fixed as 4, whereas the quantity around the axis can be 5, 7, 9, 12 and 16 tubes. The working fluid considered in this study is a mixture of noble gases He-Xe with a molecular weight of 40 g/mol, whereas Inconel alloy 617 is applied as the recuperator material. The optimization procedure was based on the entropy generation minimization and the heat exchanger effectiveness, using the Computational Fluid Dynamics (CFD) technique to obtain the flow field. Optimum mass flow rates are obtained for all the geometries at the points of minimum entropy generation number, around which lie the ranges of tested mass flow rates. The ratio between the entropy generation number and effectiveness associated with the optimum mass flow rate is considered a performance evaluation criterion, and the dependence of this parameter with exchanger mass is assessed in order to select the most suitable geometry for the studied application. This analysis leads to the optimum design point at the geometry of 9 tubes around the recuperator axis, yielding a lost available work of 929.76 W for an ambient temperature of 298 K.